2017
DOI: 10.1111/cmi.12771
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriouter inflammatory protein A (OipA) suppresses apoptosis of AGS gastric cells in vitro

Abstract: Outer inflammatory protein A (OipA) is an important virulence factor associated with gastric cancer and ulcer development; however, the results have not been well established and turned out to be controversial. This study aims to elucidate the role of OipA in Helicobacter pylori infection using clinical strains harbouring oipA "on" and "off" motifs. Proteomics analysis was performed on AGS cell pre-infection and postinfection with H. pylori oipA "on" and "off" strains, using liquid chromatography/mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 162 publications
(194 reference statements)
0
16
0
Order By: Relevance
“…Damage induced by OipA presence is usually correlated with a greater risk of GC onset or peptic as well as duodenal ulcer disease and depends on the duration of infection and a dose of H. pylori [222,223]. The synthesis of CagA and VacA is believed to be regulated by OipA expression [224]. OipA is more prevalently detected in the gastric biopsy specimens obtained from patients with gastric precancerous lesions than those with gastritis alone.…”
Section: Outer Inflammatory Protein Amentioning
confidence: 99%
“…Damage induced by OipA presence is usually correlated with a greater risk of GC onset or peptic as well as duodenal ulcer disease and depends on the duration of infection and a dose of H. pylori [222,223]. The synthesis of CagA and VacA is believed to be regulated by OipA expression [224]. OipA is more prevalently detected in the gastric biopsy specimens obtained from patients with gastric precancerous lesions than those with gastritis alone.…”
Section: Outer Inflammatory Protein Amentioning
confidence: 99%
“…Several studies have reported that OipA can increase the secretion of interleukin-8 (IL-8) and other inflammatory factors to cause neutrophil infiltration, aggravating the inflammation in the stomach and helping H. pylori to colonize, and this is why it is called an outer inflammatory protein [42,44]. OipA also inhibits the apoptosis of gastric cells [45], reducing the incidence of β-catenin nuclear translocation and cancer when the oip gene is switched off [46]. However, an in vitro study showed that OipA did not induce an increase in IL-8 expression [42].…”
Section: Oipa (Hoph)mentioning
confidence: 99%
“…SGC-7901 cells were microscopically enumerated using an improved Neubauer counting chamber. Monolayer SGC-7901 cells in a 6-well plate (10 5 /well) were incubated with H. pylori at a multiplicity of infection of 50:1 for 12 h at 37°C and 10% CO 2 , as previously described (25).…”
Section: Methodsmentioning
confidence: 99%